Pengaruh Pendapatan Asli Daerah (PAD), Dan Dana Alokasi Khusus (DAk) Terhadap Alokasi Belanja Modal - Vania Rakhmadhani; Lilis Saidah Napisah (LPPM POLITEKNIK LP3I BANDUNG, 2024)
This research was conducted to determine: 1) The influence of local original income on capital expenditure in Cimahi City. 2) The influence of Special Allocation Funds on Capital Expenditures in Cimahi City. 3) The influence of Regional Original Income and Special Allocation Funds together on Capital Expenditures in Cimahi City. The population in this research is the Cimahi City Provincial Government APBD Financial Report for 2011-2020, while the sample used is based on a non-probability sampling technique by sampling using saturated sampling. This research uses quantitative methods using descriptive and verification approaches. The data analysis method used is multiple linear regression analysis. Based on the research results, it shows that simultaneously there is a significant influence between Original Regional Income and special allocation funds on capital expenditure in the Cimahi City Government in 2011-2020. The magnitude of the influence of these two variables on capital expenditure is influenced by other variables outside the research. Partial research results show that Regional Original Income and Special Allocation Funds have a positive and significant effect on capital expenditure in the Cimahi City Government in 2011-2020.